A Comparison Between Shale Gas in China and Unconventional Fuel Development in the United States: Health, Water and Environmental Risks - Paolo D. Farah; Riccardo Tremolada (Fondazione Eni Enrico Mattei (FEEM), 2013)
China is appraised to have the world's largest exploitable reserves of shale gas, although several legal, regulatory, environmental and investment-related issues will likely restrain its scope. China's capacity to successfully face these hurdles and produce commercial shale gas will have a crucial impact on the regional gas market and on China's energy mix, as Beijing strives to decrease reliance on imported oil and coal, while attempting to meet growing energy demand and maintain a certain level of resource autonomy. The development of the unconventional natural gas extractive industry will also endow China with further negotiating power to obtain more advantageous prices from Russia and future liquefied natural gas (LNG) suppliers. This paper, adopting a comparative perspective, underlines the trends learned from unconventional fuel development in the United States, emphasizing their potential application to the Chinese context in light of recently signed production-sharing contracts between qualified foreign investors and China. The wide range of regulatory and enforcement problems in this matter are accrued by an extremely limited liberalization of gas prices, lack of technological development, and political hurdles curbing the opening of resource extraction to private investors. These issues are exacerbated by concerns related to the risk of water pollution deriving from mismanaged drilling and fracturing, absence of adequate regulation framework and industry standards, entailing consequences on social stability and environmental degradation.
Keywords: A12; A13; D40; D62; D81; F10; F13; F18; H23; K32; K33; Q4; Q40; Q41; Q42; Q43; Q48; F1; F13; F40; L95; Q3; Q30; Q32; Q33; Q25; 330; Shale Gas; Unconventional Fuel; China; U.S.A.; Health; Water; Environmental Risks